MODALITY ON PRESIDENT TRUMP’S SPEECH ON CORONAVIRUS PANDEMIC - Syafrida . Matondang; Anni Holila Pulungan (Universitas Negeri Medan, 2022)
This study investigates modality used in the Trumps’ speech on coronavirus pandemic addressed in the types of modality, value of modality and the explanation on the modality context. This study was analyzed qualitatively. The data of this study is the clause that consists of modality on President Trump’s speech, and sources of data is taken from www.nytimes.com. The data collected by applying a documentary technique. The finding reveals that the speakers use modalization of probability in their speech. The use of modality realized by modal auxiliary that commonly used by the speaker in the speech is sub modalization–probability. The reason that the speakers use modality is typically the modalization used to convey/persuade the listener of the speaker talk about the future political event that have not happened yet and unpredictable things.